ARTIFICIAL INTELLIGENCE DALAM PEMBELAJARAN FIKIH: MENINGKATKAN MOTIVASI DAN PEMAHAMAN SISWA - Nuravni, Lisvia; Hernawati; Somantri, Ace (LPPAIK Universitas Muhammadiyah Bandung, 2025)
This study aims to determine the effect of the use of virtual media based on Artificial Intelligence (AI) on students' learning motivation and understanding in fiqh learning at MA Baabussalaam Bandung. This study uses a quantitative approach with an associative research type. Data were collected by distributing questionnaires to 51 students, with 49 data that were eligible to be processed using the SPSS for Windows 10 program. The independent variable in this study is the use of AI virtual media, while the dependent variables consist of students' learning motivation and understanding. The results of the study showed that there was a positive and significant effect between the use of AI virtual media on students' learning motivation, as indicated by the Spearman correlation value of 0.779 (p <0.01) and the results of the significant linearity test. This proves that AI virtual media can increase students' interest and enthusiasm in learning fiqh. Meanwhile, the use of AI media also has an effect on students' understanding, but not as strong as its effect on learning motivation. The results of the regression test showed a significant effect (p <0.05), but the correlation was not statistically significant (p>0.05). Thus, AI virtual media has great potential in improving the quality of fiqh learning, especially in terms of students' learning motivation.